JUKUGO KANJI 金 KIN, 貨 KA, 銭 SEN YANG TERKAIT DENGAN MAKNA UANG - Mohammad Hilman Sahrizal; Yanti Hidayati; Aulia Arifbillah Anwar (Faculty of Economics, Law, and Humanities, 2019)
This study discusses the relationship between the meaning of kanji 金 (kin), 貨 (ka), 銭 (sen) in the kanji jukugo which has the meaning of money in Indonesian. This research uses descriptive qualitative method. The researcher uses this method because basically this research is a qualitative research. In addition, this method is also considered appropriate enough to approach the problem to be studied. The technique that will be carried out in collecting data in this research is conducting a literature study. The data analysis technique used is describing each kanji vocabulary contained kanji 金 (kin), 貨 (ka), 銭 (sen) then analyzing how the relationship between the meaning of kanji’s foms, then analysing into a table that illustrates the meaning of each starch based on the form original from the vocabulary of the kanji contained kanji 金 (kin), 貨 (ka), 銭 (sen) which shows the meaning of money. This study has including that each kanji can show the function and structure of the meaning of the money shown, and from the translation of the kanji based on the meaning of the author's relationship can know the meaning of words based on the pattern and meaning of the kanji Jukugo’s forms.